Gene-Regulatory Potential of 25-Hydroxyvitamin D3 and D2 - Hanel, Andrea; Veldhuizen, Cor; Carlberg, Carsten (Frontiers in Nutrition, 2022)
Human peripheral blood mononuclear cells (PBMCs) represent a highly responsive primary tissue that is composed of innate and adaptive immune cells. In this study, we compared modulation of the transcriptome of PBMCs by the vitamin D metabolites 25-hydroxyvitamin D3 (25(OH)D3), 25(OH)D2 and 1α,25-dihydroxyvitamin D3 (1,25(OH)2D3). Saturating concentrations of 1,25(OH)2D3, 25(OH)D3 and 25(OH)D2 resulted after 24 h stimulation in a comparable number and identity of target genes, but below 250 nM 25(OH)D3 and 25(OH)D2 were largely insufficient to affect the transcriptome. The average EC50 values of 206 common target genes were 322 nM for 25(OH)D3 and 295 nM for 25(OH)D2 being some 600-fold higher than 0.48 nM for 1,25(OH)2D3. The type of target gene, such as primary/secondary, direct/indirect or up-/down-regulated, had no significant effect on vitamin D metabolite sensitivity, but individual genes could be classified into high, mid and lower responders. Since the 1α-hydroxylase CYP27B1 is very low expressed in PBMCs and early (4 and 8 h) transcriptome responses to 25(OH)D3 and 25(OH)D2 were as prominent as to 1,25(OH)2D3, both vitamin D metabolites may directly control gene expression. In conclusion, at supra-physiological concentrations 25(OH)D3 and 25(OH)D2 are equally potent in modulating the transcriptome of PBMCs possibly by directly activating the vitamin D receptor.